From cents to half-cents and its liquidity impact. Issue 3 (10th November 2014) - Anderson, Hamish D.; Peng, Yuan
Abstract : Purpose: – The purpose of this paper is to examine the impact on stock liquidity following the reduction of minimum tick size from $0.01 to $0.005 for a selection of dual-listed and property stocks on the New Zealand Exchange (NZX) during 2011. Design/methodology/approach: – Various liquidity measures were examined six months either side of the change in minimum tick size for the eligible stocks and these were compared to a sample of stocks matched on similar liquidity characteristics. Liquidity measures examined in the paper include quoted and effective spread, volume, depth and binding-constraint probability. Findings: – After controlling for firms matched on similar pre-period liquidity characteristics both spread and depth decline significantly. Evidence that small firms experience significant declines in trading activity was also found, and while firms with higher binding-constraints probability have greater declines in spread, their decline in depth is greater still. Research limitations/implications: – The small sample of 17 stocks eligible for the $0.005 minimum tick size potentially impacts on the strength of the statistical analysis. As such, it is harder to detect statistically significant changes in liquidity. Practical implications: – These findings have important implications for policymakers as the hoped for benefits of smaller tick increments may only be fully realized by larger more active stocks. Originality/value: – The paper examines the impact of a change in minimum tick size on eligible New Zealand Exchange (NZX) stocks to determine whether it meet the stated NZX goal of boosting liquidity.